Smartphones, Social Networks, and Fake News: Institutional Economics Approach to Decision Making in the Twenty-First Century. Issue 2 (3rd April 2021) - Almeida, Felipe; Mortari, Valéria
Abstract: Institutional Economics relies on a practical understanding of decision making. Institutions, habits, and cumulative causation introduce not only information, but also how to make decisions. Today's world offers new challenges for the practical comprehension of decisions. Since the end of the twentieth century, the internet has drastically increased the quantity of information available to a decision-maker. Furthermore, the beginning of the twenty-first century brought a boom in social networking, which changed interactions, habits building, institutional spreading, and emulative logic. This study thus aims to approach the twenty-first century information technology to Institutional Economics' reading of decision making.